Improvement of fluvastatin bioavailability by loading on nanostructured lipid carriers - El-Helw, Abdel-Rahim M (Int J Nanomedicine, 2015)
The aim of this study is to prepare fluvastatin nanostructured lipid carriers (FLV-NLCs) in order to find an innovative way to alleviate FLV-associated disadvantages. The limitations include poor solubility and extensive first-pass metabolism, resulting in low (30%) bioavailability and short elimination half-life (1–3 hours). FLV-NLCs were prepared by hot emulsification–ultrasonication method. Ten runs were created by three-level factorial design (32) to optimize FLV-NLCs formulation process. In this study, two factors, four responses, and three-level factorial design were endorsed. The studied variables were lipid:oil ratio (X(1)) and sonication time (X(2)). However, the responses parameter determined the particle size (Y(1), nm), entrapment efficiency percent (EE%, Y(2)), particles zeta potential (Y(3)), and 80% of the drug release after 24 hours (X(4)). Furthermore, stability and in vivo pharmacokinetics were studied in rats. The optimized consisted formula had an average particle size of 165 nm with 75.32% entrapment efficiency and 85.32% of drug released after 24 hours, demonstrating a sustaining drug release over 24 hours. An in vivo pharmacokinetic study revealed enhanced bioavailability by >2.64-fold, and the mean residence time was longer than that of FLV. We concluded that NLCs could be promising carriers for sustained/prolonged FLV release with enhanced oral bioavailability.